ROLE GREEN FINANCING, GREEN FINTECH, AND GREEN INNOVATION TO GREEN CUSTOMER LOYALTY WITH MODERATIONGREEN TOP MANAGEMENT SUPPORT: SYSTEMATIC LITERATURE REVIEW - Elisa Septiani; Muhammad Iqbal Phase; Rosydalina Putri; Hanif .; Moh Mukri (GLORY Jurnal Ekonomi dan Ilmu Sosial, 2026)
This study aims to analyze the role of Green Financing, Green Fintech, and Green Innovation on Green Customer Loyalty with the moderating role of Green Top Management Support through the Systematic Literature Review (SLR) approach. The study uses the PRISMA method in the process of identifying, selecting, and evaluating relevant international journal articles in the period 2015–2025. Literature sources were obtained from various academic databases using keywords related to green financing, green fintech, green innovation, green customer loyalty, and green top management support. The results of the study indicate that Green Financing contributes to increasing customer loyalty through sustainable financial products and corporate environmental commitments. Green Fintech strengthens customer loyalty through the integration of financial technology innovation with sustainability values, while Green Innovation creates added value through the development of environmentally friendly products, services, and business processes. In addition, Green Top Management Support acts as a moderating variable that strengthens the relationship between Green Financing, Green Fintech, and Green Innovation on Green Customer Loyalty. Strong top management support can ensure the implementation of green strategies is carried out consistently and authentically, thereby increasing customer trust and reducing the risk of greenwashing perceptions. This study concludes that the synergy between green financing, green technology innovation, and top management commitment is an important factor in building sustainable Green Customer Loyalty in the financial sector. Keywords : Green Financing, Green Fintech, Green Innovation, Green Customer Loyalty, Green Top Management Support, Systematic Literature Review.